PENGOBATAN INFEKSI PARVOVIRUS PADA ANJING - IKW Sardjana; D. Kusumawati (The East Java Biological Society, 2004)
Treatments of canine Parvovirus have already done to 22 dogs. There were 16 dogs, one month to one years of age and 6 dogs two years to seven years of age. The results of the theraphy, were ten dogs survived and twelve dogs died due to Parvovirus infection. Fluid theraphy supported by antibiotic, antiemetic or antacids administrations were essential for Parvovirus infection in dogs. The recovery rate of this dogs was 45%.